El impacto del periodismo ciudadano en el periodismo digital, caso paro nacional 2019 - Fajardo Cachote, Cristhian Oswaldo (2020)
In the development of this Case Study, Impact of Citizen Journalism on Digital Journalism, Case of National Unemployment 2019, it was possible to verify a great impact of citizen journalism on digital journalism, this being the problem of main interest for the development of this investigation. Years ago the media could not find the great potential offered by the Internet platform, today with digital journalism all the elements and services offered by the Internet are used, with the purpose of enhancing information through a medium and in a fast and efficient In this case study, two research techniques were applied, the interview and the survey, making a list of questions from which current information about social development was extracted regarding the two variables under study. In this case, study; the direct beneficiaries are citizens, making known the parameters for a responsible and true journalism. It is proposed as a solution proposal, to train citizens on issues of information distribution, to avoid the spread of false news.